Endoscopic Band Ligation in Patients with Variceal Bleeding - Belbase, Narayan Prasad; Jalan, Aditya; Upadhya, Hari Prasad; Mishra, Rohit; Karki, Mukesh; Kumar, Sujit (Birat Journal of Health Sciences, 2018)
Introduction: Esophageal varices (EV) affect about 50% of patients with liver cirrhosis. Mortality rate from the initial EV bleeding can rise up to 30% in patients with advanced liver disease and large varices. Several RCTs have shown endoscopic variceal banding to be more effective than sclerotherapy for the long-term prevention of variceal bleeding. Objective: This study was conducted to see the outcome of endoscopic banding in the management of esophageal varices in Nepalese population. Methodology: This was a prospective observational study conducted in the Department of Surgical Gastroenterology, College of Medical Sciences and Teaching Hospital (COMS-TH), Bharatpur, Nepal over a period of 2 years. Patients attending the COMS emergency/surgical OPD with history of UGI bleed with features consistent with portal hypertension during this period were enrolled. The endoscopic variceal band ligation was done based on similar principles applied to Barren and ligation in the treatment of internal haemorrhoids. Results During this period of two years 50 patients were analysed. The mean age of the study subjects was 52.26+/-12.80 years and male predominance was seen (M:F=42:8). Alcoholic chronic liver disease (CLD) (74%) was the most common cause of portal hypertension. Child's B score was seen among 54%, grade III varices were seen in 36% and grade II in 32%. Acute bleeding of varices was present in nine (18%) cases. On an average 3.8 sessions were required to obliterate the varices. Control of acute bleed and variceal eradication was seen in 77.78% cases and in 96% cases respectively. Complications following banding were seen in 20% cases. Mortality was seen in two (4%) cases. Conclusions: Alcoholic cirrhosis was the most common cause of portal hypertension and endoscopic banding of oesophageal varices in Nepalese population had comparable eradications, complications and recurrences with similar other studies conducted in other parts of the world. BJHS 2018;3(1)5 : 320-324